Efektivitas Study Club Terhadap Peningkatan Prestasi Belajar Mahasiswa S1 Fisioterapi Universitas Muhammadiyah Surakarta - Arif Pristianto; Citradewi Ratnadilla (Universitas Muhammadiyah Surakarta, 2021)
Study club is an interest-based community that become the hallmark of lectures and Physiotherapy studies at University of Muhammadiyah Surakarta. The academic department of study club consists of Sport Physio UMS, Physiopedy UMS, Geriatric Wellness Club, and Neurological Physiotherapy Study Club. The Purpose was to determine the influence of the study club on improving the learning achievement and to find out the increasing on learning achievement of University of Muhammadiyah Surakarta 2016 undergraduate class physiotherapy that taking part of study club. The type of research based on the method is survey and according to the level of explanation is descriptive with a sample of 102 respondents. Hypothesis testing using simple linear regression analysis and descriptive statistics. The results using simple linear regression obtained the value of R (correlation) of 0.496 which means a positive correlation between student achievement with study club, along with the greater of semesters in attending a study club, the learning achievement increases. The value of R2 (coefficient of determination) which shows the contribution of study clubs to an increase in learning achievement by 24.6%. The constant value is 3.218 with the study club regression coefficient of 0.115, which means that the constant value for students who do not take the study club is 3.218 and will get a grade point increase of 0.115 each following a semester club study. In general, there is an increase in the average student achievement index taking part in the study club.